Pengaruh Pendidikan Agama dalam Keluarga dan Teman Sebaya terhadap Budaya Religius Siswa SMA se-Kecamatan Muara Muntai Kutai Kartanegara - Erhansyah, Erhansyah (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
The religious culture is one of the main elements in the effort to bring children toward religious education, and that education begins with the family, then the family of religious education in particular will be key also in the formation of religious culture in children or students. Education key lies in spiritual education in the sense of nuanced religiuitas education, religious education for children. Because of religious education in the family can make the students motivated to behave religion in school. Education is either associated with Allah (hablumminallah) and relationships with other human beings (hablumminannas) and also the human relationship with the environment. This research was conducted with a quantitative approach that is descriptive correlational that is looking for a relationship and influence of the independent variables religious education in the family (X1) peers (X2) the religious culture of the dependent variable (Y), both individually and together. The results of this study indicate that each independent variable has a positive correlation and influence signifikan namely religious education in the family (0,266) and the religious culture of schools (0,356). Are connected with the same significant difference between religious education in families with peers in religious culture with a value of R 0,368, R2 0,135. This means that the percentage contribution of the influence of the independent variables (religious education in the family and peers) on the dependent variable (religious culture) of 13,5% From the results of numerical analysis it can be described that religious education in the family and peers have an influence on religious culture and the influence of peers is greater than religious education in the family's religious culture.